2021
DOI: 10.1177/2192568220976089
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Disc Herniation and Preoperative Modic Changes: A Prospective Analysis of the Clinical Outcomes After Microdiscectomy

Abstract: Study design: Prospective comparative cohort study. Objectives: The study aims to elucidate the relationship between Modic endplate changes and clinical outcomes after a lumbar microdiscectomy. Methods: Consecutive patients undergoing microdiscectomy for lumbar disc herniation (LDH) were prospectively studied. Pre-operative clinical and radiological parameters were recorded. The pain was assessed by Numeric pain rating scale (NPRS), and functional assessment by Oswestry Disability Index (ODI). Minimal clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Kumarasamy et al [ 21 ] prospectively followed 309 patients undergoing microdiscectomy, 86 of whom had MC. The patients in the MC group had worse postoperative numeric rating scale (NRS) back pain (1.6 to 1.1, p = 0.001), although the overall improvement in both groups was 4.3 points, indicating that there was no difference in the magnitude of overall improvement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kumarasamy et al [ 21 ] prospectively followed 309 patients undergoing microdiscectomy, 86 of whom had MC. The patients in the MC group had worse postoperative numeric rating scale (NRS) back pain (1.6 to 1.1, p = 0.001), although the overall improvement in both groups was 4.3 points, indicating that there was no difference in the magnitude of overall improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported values for ODI [ 21 , 23 , 44 , 45 , 50 ], and four studies reported VAS back pain [ 21 , 44 , 45 , 50 ]. A meta-analysis was performed among these studies and identified no significant associations between MC and either postoperative VAS back pain or ODI ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MCs are the specific imaging manifestations characterized by CLBP as a clinical feature [ 39 ]. The underlying mechanism remains unclear and debated (mechanical, local infection, genetic) [ 40 , 41 , 42 ]. For patients with MCs, the clinical approach remains based on the treatment principles of CLBP, with a focus on reducing pain intensity.…”
Section: Discussionmentioning
confidence: 99%